Supplement to the knowledge of the genus Scaphidium Olivier of East China (Coleoptera: Staphylinidae: Scaphidiinae) - Tu, Yue-Ye; Tang, Liang (Zootaxa, 2017)
A new species, Scaphidium ahrensi sp. n., is described from Fujian Province and its diagnostic characters are illustrated. Scaphidium vicinum Pic, 1915 is discovered from mainland China for the first time. A modified key is given to accommodating these two species.